The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10517-017-3845-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Induced Pluripotent Cells from Stromal Liver Cells of Patients with Alcoholic Cirrhosis

Abstract: Stromal liver cells obtained from liver biopsy specimens of a patient with alcoholic cirrhosis can proliferate for a long time in culture passing more than 30 passages. In the course of culturing from early to late passages, acceleration of cell proliferation, decrease of the expression of some markers, and loss of hepatogenic differentiation potential were observed. On passage 30, induced pluripotent stem cells were obtained from these cells and comparative analysis of adipogenic and hepatic differentiation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Some studies show that under standard adipogenic conditions [3] liver MSCs differentiate into adipocytes and accumulate lipid vacuoles [22,28,92], while other works deny this fact [20,21,72]. In our work, we demonstrated that in a population of liver MSCs isolated from the liver of patients with alcoholic cirrhosis, a proportion of cells are able to accumulate lipid droplets 3 weeks after the induction of adipogenic differentiation in a growth medium supplemented with insulin, IBMX (3-isobutyl-1-methylxanthine), dexamethasone, and indomethacin [93] (Figure 2).…”
Section: Properties and Therapeutic Potential Of Human Liver Mscsmentioning
confidence: 63%
“…Some studies show that under standard adipogenic conditions [3] liver MSCs differentiate into adipocytes and accumulate lipid vacuoles [22,28,92], while other works deny this fact [20,21,72]. In our work, we demonstrated that in a population of liver MSCs isolated from the liver of patients with alcoholic cirrhosis, a proportion of cells are able to accumulate lipid droplets 3 weeks after the induction of adipogenic differentiation in a growth medium supplemented with insulin, IBMX (3-isobutyl-1-methylxanthine), dexamethasone, and indomethacin [93] (Figure 2).…”
Section: Properties and Therapeutic Potential Of Human Liver Mscsmentioning
confidence: 63%
“…It is possible that the coculture of hiPSC-derived HLCs and hiPSC-derived HSC-like cells partially mimics the process of liver fibrosis [Coll et al, 2018]. The authors Asgari et al, 2010;Ghodsizadeh et al, 2010;Rashid et al, 2010;Ordonez and Goldstein, 2012;Pournasr and Duncan, 2017;Coll et al, 2018;Genova et al, 2018;Overeem et al, 2019NAFLD Soga et al, 2015Kholodenko et al, 2017;Chien et al, 2018;Graffmann et al, 2018a, b Cholangiopathies Graffmann et al, 2016Wruck et al, 2017 showed that using 3-dimensional (3D) culture with hepatocytes, HSCs derived from hiPSCs were transformed into myofibroblasts via treatment with transforming growth factor-β, thioacetamide, and acetaminophen in vitro. Activated iPSC-derived HSCs secrete procollagen [Coll et al, 2018], which contributes to liver fibrosis.…”
Section: Modeling With Ipscs From the Patient Modeling In Liver Fibrosismentioning
confidence: 99%
“…Recently, several other liver-specific disease iPSCs, such as FH, glycogen storage diseases, Crigler-Najjar syndrome, hereditary tyrosinemia type 1, Gaucher disease, Niemann-Pick disease type C, A1AT deficiency, and alcoholic cirrhosis have been launched [Ghodsizadeh et al, 2010;Rashid et al, 2010;Soga et al, 2015;Kholodenko et al, 2017]. Their results demonstrated that hiPSC-derived HLCs can be generated from multiple patients of varied genetic and disease backgrounds, and their system is proved to be an efficient methodology for the early-stage safety and therapeutic screening of liver-targeted compounds of potential relevance to the pharmaceutical industry.…”
Section: Modeling With Ipscs From the Patient Modeling In Liver Fibrosismentioning
confidence: 99%
“…Unlike conventional immunoglobulins, these smaller biomolecules take several pharmacokinetics advantages over whole antibodies including better penetration into tissues, faster clearance for imaging purposes and generally lower immunogenicity. On the other hand, the absence of the Fc domain and the small size results in a shorter half-life compared to full-length antibodies [2].…”
Section: Introductionmentioning
confidence: 99%